Insulin degludec overdose may lead to long‐lasting hypoglycaemia through its markedly prolonged half‐life. Issue 2 (14th January 2018) - Uchida, J.; Oikawa, Y.; Katsuki, T.; Takeda, H.; Shimada, A.; Kawai, T.
What's new?: We describe a woman with long‐lasting hypoglycaemia attributable to insulin degludec (IDeg) overdose and the markedly prolonged IDeg half‐life. There are currently no reports on the half‐life of IDeg induced by overdose. Overdose of IDeg (300 units, 4.34 units/kg) increased its half‐life by ˜1.6 times compared with its half‐life after standard doses (0.4–0.8 units/kg), which probably led to long‐lasting hypoglycaemia. The immunoreactive insulin derived from IDeg injection remained in the blood for ˜400 h. Physicians should be aware of the possibility of unexpected long‐lasting hypoglycaemia as a result of IDeg overdose. Abstract: Background: Overdose of insulin often causes long‐lasting severe hypoglycaemia. Insulin degludec has the longest duration of action among the available insulin products; thus, an overdose of insulin degludec can lead to long‐lasting hypoglycaemia. In the present paper, we report the case of a woman with long‐lasting hypoglycaemia attributable to insulin degludec overdose and markedly prolonged insulin degludec half‐life. Case report: A 64‐year‐old woman with Type 2 diabetes receiving insulin therapy was taken to an emergency department because of disturbed consciousness 21 h after self‐injection of 300 units of insulin degludec (4.34 units/kg). Her plasma glucose level was 2.3 mmol/l. She received repeated intravenous boluses of dextrose for 43 h with continuous intravenous dextrose infusion, but no improvement in long‐lasting hypoglycaemia or consciousness was observed. Considering the possibility of adrenal insufficiency, intravenous dexamethasone was administered, and her plasma glucose levels subsequently remained above 5.5 mmol/l without intravenous dextrose boluses. She gradually regained consciousness. A total of 34 h after the overdose, her plasma immunoreactive insulin levels were markedly increased and then gradually declined over ~400 h. The insulin degludec half‐life was 40.76 h. Conclusion: Although the reported half‐life of insulin degludec in the body is ~25 h when administered in standard doses (0.4–0.8 units/kg), no study has investigated its half‐life after overdose. In the present case, the half‐life of insulin degludec was ~1.6 times longer than that observed with standard doses, probably leading to long‐lasting hypoglycaemia. Physicians should be aware of the possibility of unexpected long‐lasting severe hypoglycaemia resulting from insulin degludec overdose.